Legal and practical issues in strata management: roles of developers and commissioner of buildings in Peninsular Malaysia - Mohamad, Nor Asiah; Sufian, Azlinor (2013)

(untitled)
This study looks at the roles of the developers and the COB in the management of strata properties under the Housing Development Act 1966 (HDA) the Building and Common Property Act (Management and Maintenance) Act 2007 (BCPMMA), the Strata Titles Act 1985 (STA) as well as the new Strata Management Act 2013 (SMA). The discussion revolves around the issues of defect liability periods, vacant possession, late delivery, handing over of management, management of common property, funds as well as settlement of dispute under the proposed Strata Management Tribunal (SMT).